PENGARUH DIGITAL MARKETING TERHADAP PERTUMBUHAN USAHA MIKRO KECIL MENENGAH (UMKM) DI ERA DIGITAL. - Yusuf Arnawi Silaban; Sepman Teguh zega; Renhad Tambunan; Rossy Perwarissa Marpaung; Patricia Herpayanti Rajagukguk; Nalom Siagian (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The development of digital marketing offers numerous opportunities for MSMEs to enhance their business growth. This study aims to analyze the impact of digital marketing on MSME growth today. The method used is a qualitative method, collecting data through interviews and direct observation of MSMEs. The results show that the use of social media and digital platforms can increase brand awareness, boost sales, and expand the market. This program provides digital training, assistance with access to capital, and technical support so that MSMEs can more easily adapt to technological changes. Studies on the impact of the digital economy on MSMEs are increasingly relevant amidst the rapid digital transformation. Research shows that digitalization can increase MSME productivity and operational efficiency, ultimately driving economic growth.